Qarounispora grandiappendiculata gen. et sp. nov. (Halosphaeriaceae, Microascales) from Qaroun Lake, Egypt - Nourel-Din, Ali A. H.; Abdel-Aziz, Faten A.; Abdel-Wahab, Mohamed A. (Phytotaxa, 2022)
An ascomycete collected from wood submerged in Qaroun Lake, El-Faiyum governorate, Egypt, is described as a new genus in the family Halosphaeriaceae. Multigene analyses based on LSU, SSU and ITS rDNA placed the new fungus as a distinct branch within the family. The new genus is characterized by its yellow to orange-brown ascomata, thin-walled, semi-persistent asci, hyaline to yellow-orange, thick-walled, distoseptate ascospores with one polar appendage that is amorphous in structure, large in size and irregular in shape.